2007
DOI: 10.1007/s11060-007-9473-5
|View full text |Cite
|
Sign up to set email alerts
|

Conventional MRI cannot predict survival in childhood diffuse intrinsic pontine glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) of childhood has a dismal prognosis. Clinical trials of new agents are vital and it is essential that the correct endpoints and disease assessments are chosen. A retrospective review of magnetic resonance imaging (MRI) scanning in a pure population of DIPG was undertaken. Baseline diagnostic MRI findings included; local tumour extension in upper medulla (74%) or midbrain (62%), metastatic disease (3%), basilar artery encasement (82%), necrosis (33%), intratumoural haemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 30 publications
3
63
1
Order By: Relevance
“…1,5 Thus, the impact of MRI findings on treatment decisions for brainstem tumors is very high, but the accuracy of MRI-based diagnosis of diffuse brainstem gliomas has not been fully verified by histopathological findings. 8 Thus, some authors have reported that all diffuse brainstem gliomas located above the medulla behave as high-grade astrocytomas, and histological grade is not a significant factor for the survival of these patients. 1,4,5,18,20 Few studies have been conducted concerning prognosis and prognostic factors in brainstem gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Thus, the impact of MRI findings on treatment decisions for brainstem tumors is very high, but the accuracy of MRI-based diagnosis of diffuse brainstem gliomas has not been fully verified by histopathological findings. 8 Thus, some authors have reported that all diffuse brainstem gliomas located above the medulla behave as high-grade astrocytomas, and histological grade is not a significant factor for the survival of these patients. 1,4,5,18,20 Few studies have been conducted concerning prognosis and prognostic factors in brainstem gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional MRI has been shown to be insufficient in predicting clinical outcome. 142 The limited information currently available on molecular pathways involved in the tumorigenesis of these tumors limits a rational approach to test new agents. To date, new trials are often designed based on knowledge gained from other adult or pediatric high-grade glioma experiences.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the past 40 years, the outcome of patients with DIPG has remained unchanged, with less than 10% of the patients being alive 2 years from diagnosis (1,2). Given the lack of gadolinium uptake on MRI in DIPG tumors (3,4), it is plausible that the blood-brain barrier (BBB) in DIPG often remains intact which might explain the resistance to systemic chemotherapy in these patients.…”
Section: Introductionmentioning
confidence: 99%